The Contribution of Managerial Competence and Leadership of Madrasah Heads to Teacher Performance and Quality of Education: (Study on Madrasah Aliyah in Tangerang Regency) - Sarifudin, Aip; Prastya Firmansyah, Ichsan; Apriana Markus, Mira; Az-Zahra, Fathimah; Haniyyah, Haniyyah; Deviputri Suwandi, Safna; Saefullah, Saefullah; Winanti, Winanti; Kamar, Karnawi; Farhan, Akhmad (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
Problems that occur in the field show that the performance of teachers in several Aliyah Madrasah in Tangerang Regency is still not optimal, which is reflected in the low discipline in the implementation of tasks, lack of innovation in learning methods, and the achievement of student learning outcomes that are not in accordance with the set educational quality standards. This condition indicates the existence of managerial and leadership factors of madrasah heads that need attention, considering the strategic role of madrasah heads as educational leaders in mobilizing all school resources to achieve educational goals, this study aims to analyze the contribution of leadership management to the governance of Islamic educational institutions by focusing on its influence on teacher performance and education quality. In the research conducted in this madrasah, a quantitative method was used with a survey research design on 85 teachers from three Aliyah Madrasah in Tangerang Regency.